Dampak Tingkat Utang dan Profitabilitas pada Penghindaran Pajak dengan Ukuran Perusahaan Memainkan Peran Moderating - Erlinda Tri Hapsari; Hasim As’ari (PT Bone Jaya Kreatif, 2024)
Taxes are the largest revenue for the Indonesian state, but efforts to optimize revenue from this sector have several obstacles, one of the obstacles in the context of optimizing tax revenue is the existence of tax avoidance by the company. This study aims to prove the effect of leverage and profitability on tax avoidance with company size as a moderating variable. In this study using agency theory with the population in this study, namely all chemical sector industrial manufacturing companies listed on the Indonesia Stock Exchange 2020. The sample used purposive sampling method which amounted to 33 companies. This research uses quantitative methods, and is processed using SPSS version 26 software with descriptive statistical methods, classical assumption tests, t tests and regression analysis of moderating variables. The results of this study indicate that Leverage, Profitability, and Company Size have no effect on Tax Avoidance. Company Size is unable to moderate the relationship between Leverage and Tax Avoidance, Company Size is unable to moderate the relationship between Profitability and Tax Avoidance.